A Legacy of Cunning Rhetorical Agility: Métis Polymorphism in the Protest Rhetoric of Sojourner Truth and Sarah Grimké. Issue 2 (3rd April 2022) - Price-McKell, Cheryl
Abstract: In Greek mythology, Metis's cunning intelligence and polymorphism are crucial in Zeus's victory over the Titans. However, the paranoid god eventually swallows Metis and claims her cunning intellect as his own—an act analogous to the patriarchal consumption of women's voice. The rhetorical concept of métis derived from this myth refers to wily, cunning, and polymorphic intelligence. This article explicates the rhetorical concept of métis and argues that women have employed métis polymorphic rhetoric throughout history to negotiate intersecting oppressions, protest injustice, and engender change. By reexamining the protest rhetoric of early feminist activists Sojourner Truth and Sarah Grimké and connecting their tactics to contemporary scholarship on feminist activism, this article draws attention to métis as a consistent determinant and a valuable theoretic framework already residing under the surface of much feminist rhetorical inquiry.